Ann Johnson, fall '99 - Johnson, Annet al (1999)
An annotated list of birds sighted by Ann Johnson dated December 1, 1999. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1999. Epson - sheet feed